O terrorismo, a luta contra o terror e o direito internacional dos direitos humanos - Guerra, Bernardo Pereira de Lucena Rodrigues (2008)
The purpose of this study is to analyze the impact of the battle against Terrorism and Terror on the Human Rights International Law. From the constitution of a mentality arisen post-Second World War, with its fundamental characteristics, and the most relevant Human Rights international instruments, it is asserted that Terrorism and the battle against Terror have represented an enormous challenge not the say the biggest one to Human Rights International Law. On the twenty-first century, humanity has witnessed the rebirth of an ancient phenomenon, re-dimensioned on its characteristics and proportions: the globalized and trans-national Terrorism. There are basically two actors directly related to contemporary Terrorism: the Islamic fundamentalism and the United States from George W. Bush doctrine. Although there are many international conventions about Terrorism, its provisions are not sufficient to combat the phenomenon, mainly due to the absence of an accurate and clear definition of Terrorism. The risks of a unilateral anti-Terrorism politics are extremely oppressive for humanity, as they are based on Human Rights violations, torture, and arbitrary detention of individuals for indefinite time, vilification on the innocence presumption, on the adversary system and on full defense. Not to mention the use of lies and the figure of the objective enemy as domination means. Considering this scenario, it is indispensible that the fight against Terrorism operates accordingly to Human Rights International Law, with full respect to Human Rights fundamental core and to the nondiscrimination principle, through the adoption of a global strategy against Terrorism, based on five principles. Humanity truly and deeply needs to experience the freedom from want, the freedom from fear and the freedom to live in dignity